2019
DOI: 10.1021/acs.chemmater.8b04172
|View full text |Cite
|
Sign up to set email alerts
|

Solid Polymer Electrolytes for Lithium Metal Battery via Thermally Induced Cationic Ring-Opening Polymerization (CROP) with an Insight into the Reaction Mechanism

Abstract: We report the synthesis of solid polymer electrolytes (SPEs) using a thermally induced and a lithium salt catalyzed cationic ring-opening polymerization (CROP) technique. A synergistic approach using two salts such as lithium tetrafluoroborate-LiBF4 and lithium bis­(tri­fluo­ro­meth­ane sulfonyl)­imide-LiTFSI has assured a complete monomer to polymer conversion and fast reaction kinetics during the CROP process. The initiation mechanism of lithium salt-induced CROP is elucidated using molecular dynamic simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 82 publications
(137 reference statements)
2
58
1
Order By: Relevance
“…In a recent report, Nair et al have proposed a different mechanism for the CROP of the diglycidyl ether oligomer that can be used for the in situ processing of SPEbased LPB by a separator assisted or a separator-free approach. 505 The reported mechanism is shown in Figure 40c, which demonstrates that the anions, in combination with a trace amount of water molecules, can initiate the CROP polymerization without decomposing into BF 3 OH and HF. This mechanism can also explain the capability of other Li-salts such Figure 40d.…”
Section: Cationic Polymerizationmentioning
confidence: 97%
“…In a recent report, Nair et al have proposed a different mechanism for the CROP of the diglycidyl ether oligomer that can be used for the in situ processing of SPEbased LPB by a separator assisted or a separator-free approach. 505 The reported mechanism is shown in Figure 40c, which demonstrates that the anions, in combination with a trace amount of water molecules, can initiate the CROP polymerization without decomposing into BF 3 OH and HF. This mechanism can also explain the capability of other Li-salts such Figure 40d.…”
Section: Cationic Polymerizationmentioning
confidence: 97%
“…Typical thermopolymerization monomers include organic metallic locenes, divinyl ether, oxitane, dimethacrylate‐based derivatives, etc. [ 159–163 ]…”
Section: Strategies and Concepts For High‐safety Materials Designmentioning
confidence: 99%
“…It has been demonstrated that lithium salt species and its concentration are crucial for "salt-in-polymer" SPEs. [132,133] Traditional lithium salts are usually employed in SPE includes LiPF 6 , [134] LiClO 4 , [130] lithium borates (LiBF 4 , LiBOB, and LiODFB), [135,136] and lithium imides (LiTFSI, LiFSI). [137] However, the low thermal stability and high moisture sensitivity of LiPF 6 , the strong oxidability of LiClO 4 , and poor solubility of lithium borates restrain their application as lithium salt in SPE.…”
Section: Blending With Lithium Saltsmentioning
confidence: 99%